Monitoring & Scheduling of A Metro Project (Bhopal) Work Using Project Management Tool Primavera P6 - Amit Namdeo; Ravindra Kumar Raj (International Journal of Scientific Research in Civil Engineering, 2021)
Arranging and Scheduling are the fundamental in the enormous foundation project like street and extension development, Metro rail projects as these are proposed for public government assistance. These activities are have various partners and enormous measure of cash, assets are contributed. Ill-advised arranging and booking prompts loss of assets, expansion in project cost and terrible postponements. Yet, because of the PC and programming advancement, it now conceivable to design these tasks utilizing programming resembles Primavera P6 and Microsoft office project.This paper manages show of metro rail project in Bhopal contrasting the two distinct stages in measure as Phase I - Subhash Nagar Phatak to Sargam Talkis and Phase II – Sargam Talkis to Saket Nagar. The task outlined expressed the benefit and added advantages of Web based primavera P6 for arranging and booking of Bhopal Metro Rail Project outlining the issues and inconveniences looked in the time span of development and accessibility of assets.
Keywords: Primavera P6 Web; Bhopal Metro; Planning; Scheduling; Monitoring And Tracking